Shape-memory polymers - Lendlein, Andreas; Behl, M. (Marc) (Advances in polymer science, 2010)
-Shape-Memory Polymers and Shape-Changing Polymers by M. Behl, J. Zotzmann, and A. Lendlein -Shape-Memory Polymer Composites by Samy A. Madbouly and Andreas Lendlein -Characterization Methods for Shape-Memory Polymers by W. Wagermaier, K. Kratz, M. Heuchel, and A. Lendlein -Shape-Memory Polymers for Biomedical Applications by Christopher M. Yakacki and Ken Gall -Controlled Drug Release from Biodegradable Shape-Memory Polymers by Christian Wischke, Axel T. Neffe, and Andreas Lendlein.